The Malay family: Beliefs and realities - Kling, Zainal (Department of Sociology, University of Calgary, 1995)
The Malay family system is the by-product of a complex interplay of historical and cultural circumstances.Historically, the Malays have been influenced by great civilizations from India, West Asia, China and recently Europe.To a degree, these civilizations left indelible marks on the social organization and, particularly, the family system.Cultural adaptation to the local environment, on the other hand, had induced the evolution of an indigenous family and kinship system distinctively different from the various exogenous influences. lnevitabily therefore, the Malay family system had integrated diverse elements within its structure and function.